Kemampuan Mengenal Lambang Bilangan Melalui Media Wayang Angka Pada Taman Kanak-Kanak Tunas Inti Kec. Tenggarong Seberang Kab. Kutai Kartanegara - Arbayah; Susilowati, Atik; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2023)
One of the areas of development taught in kindergarten is the field of cognitive development that can be obtained through counting, numering, grouping, recognizing shapes, recognizing the concept of numbers and number symbols. In terms of recognizing the symbol, the number of children in Tunas Inti Kindergarten, Tenggarong Seberang District, Kutai Kartanegara Regency is low, which is below 75%. This is due to the limited and less varied use of learning media when teaching and learning activities take place as well as activities that are less varied and monotonous. This researcher uses Classroom Action Research (PTK) as many as three cycles, each cycle is divided into four stages, namely planning, implementation, observation and reflection followed by data analysis with discriptive statistics, namely cycle-based reflection analysis. The subjects of this study were group A children in Tunas Inti Tenggarong Seberang Kindergarten who were at the age of 4-5 years who were